Circadian Rhythm of Energy Expenditure and Oxygen Consumption. (February 2014) - Leuck, Marlene; Levandovski, Rosa; Harb, Ana; Quiles, Caroline; Hidalgo, Maria Paz
Background : This study aimed to evaluate the effect of continuous and intermittent methods of enteral nutrition (EN) administration on circadian rhythm. Materials and Methods : Thirty-four individuals, aged between 52 and 80 years, were fed through a nasoenteric tube. Fifteen individuals received a continuous infusion for 24 hours/d, and 19 received an intermittent infusion in comparable quantities, every 4 hours from 8:00 to 20:00. In each patient, 4 indirect calorimetric measurements were carried out over 24 hours (A: 7:30, B: 10:30, C: 14:30, and D: 21:30) for 3 days. Results : Energy expenditure and oxygen consumption were significantly higher in the intermittent group than in the continuous group (1782 ± 862 vs 1478 ± 817 kcal/24 hours, P = .05; 257 ± 125 vs 212 ± 117 mL/min, P = .048, respectively). The intermittent group had higher levels of energy expenditure and oxygen consumption at all the measured time points compared with the continuous group. Energy expenditure and oxygen consumption in both groups were significantly different throughout the day for 3 days. Conclusion : There is circadian rhythm variation of energy expenditure and oxygen consumption with continuous and intermittent infusion for EN. This suggests that only one indirect daily calorimetric measurement is not able to show the patient's true needs. Energy expenditure is higher at night with both food administration methods. Moreover, energy expenditure and oxygen consumption are higher with the intermittent administration method at all times.